Late chronotypes, late mealtimes. Chrononutrition and sleep habits during the COVID-19 lockdown in Italy. (1st May 2022) - Bazzani, A.; Marantonio, S.; Andreozzi, G.; Lorenzoni, V.; Bruno, S.; Cruz-Sanabria, F.; d'Ascanio, P.; Turchetti, G.; Faraguna, U.
Abstract: The emerging field of chrononutrition provides useful information on how we manage food intake across the day. The COVID-19 emergency, and the corresponding restrictive measures, produced an unprecedented change in individual daily rhythms, possibly including the distribution of mealtimes. Designed as a cross-sectional study based on an online survey, this study aims to assess the chrononutrition profiles (Chrononutrition Profile Questionnaire, CP-Q) in a sample of 1298 Italian participants, during the first COVID-19 lockdown, and to explore the relationship with chronotype (reduced Morningness-Eveningness Questionnaire, rMEQ), sleep quality (Pittsburgh Sleep Quality Index, PSQI) and socio-demographics. Our findings confirm a change in eating habits for 58% of participants, in terms of mealtimes or content of meals. Being an evening chronotype and experiencing poor sleep imply a higher likelihood of changing eating habits, including a delay in the timing of meals. Also, under these unprecedented circumstances, we report that the timing of breakfast is a valuable proxy capable of estimating the chronotype. From a public health perspective, the adoption of this straightforward and low-cost proxy of chronotype might help in the early detection of vulnerable subgroups in the general population, eventually useful during prolonged stressful conditions, as the one caused by COVID-19 pandemic.